Operational aircraft maintenance routing problem with remaining time consideration - Başdere, Mehmet. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
Aircraft maintenance routing problem is one of the most studied problems in airline industry. However, most of these studies focus on nding a unique rotation that will be repeated by each aircraft in the eet with a certain lag. In practice, using a single rotation for the entire eet may not be applicable due to the stochastic environment and operational considerations in the airline industry. In this study, our aim is to develop a fast responsive methodology which provides maintenance feasible routes for each aircraft in the eet for the planning horizon with the objective of maximizing utilization of the total remaining ying time of eet. For this purpose, we formulate an integer linear programming (ILP) model by modifying the connection network representation. ILP model can be considered as an operational aircraft maintenance routing model since it provides routes for each aircraft with respect to initial states. The proposed model is solved using B&B under di erent priority settings for variables to branch on. A simulated annealing based heuristic method (compressed annealing) is utilized for the same problem and results are compared with those of B&B. Additionally, a rolling horizon based routing methodology is introduced and maintenance capacity constraints are discussed. Finally, compressed annealing method with maintenance capacity consideration is tested on the operational routing problem of a domestic airline company.
Keywords: Heuristic programming.; Simulated annealing (Mathematics); Airplanes -- Maintenance and repair -- Mathematical models.; Scheduling -- Mathematical models.